The arrival of millets to the Atlantic coast of northern Iberia - Borja González-Rabanal; Ana B. Marín-Arroyo; Emanuela Cristiani; Andrea Zupancich; Manuel R. González-Morales (Scientific Reports, 2022)
Abstract Despite being one of the most important crops in the recent prehistory of Eurasia, the arrival and exploitation of millets in the westernmost part of Europe are still largely underexplored. Here and for the first time, we report multipronged biomolecular evidence of millet consumption along the Atlantic façade of northern Iberia through a combination of radiocarbon dating, stable isotopes, and dental calculus analyses on the human individuals found in the burial site of El Espinoso cave (Asturias, Spain). The high-resolution chronological framework established for individuals placed the burials between 1235 and 1099 cal. BC. The discovery of high δ13C values on their bone collagen and the identification of polyhedral starch grains within their dental plaque underline the relevance of C4 plants in their diet and highlights the timing of the systematic consumption of millets in the Late Bronze Age. Our data support previous regional archaeobotanical evidence and establish a more precise chronology of the dispersal of millets into northern Iberia during the Bronze Age, becoming an essential crop until the arrival of maize from America after AD 1492. This study emphasizes the importance of multidisciplinary methods to ascertain the origin and development of agricultural practices during recent prehistory.